Neuropsychological assessment - Lezak, Muriel Deutsch, ....-; Howieson, Diane Black, ....-; Loring, David W., ....- (New York (N.Y.) : Oxford university press, 2004)
Well known as the 'bible' in its field, this text/reference has been thoroughly revised and updated by a team of internationally recognized and clinically experienced neuropsychologists. Drawing on their diverse interests, they provide authoritative, broad-based, and in-depth coverage of current research and clinical practice in neuropsychology. They have not, however, changed the book's overall organization. The first eight chapters present the knowledge base for understanding the principles and practice of patient-oriented, hypothesis testing neuropsychological assessment. The last 12 chapters review nearly all tests and assessment techniques discussed in previous editions plus many new ones and recent revisions of older tests. The extent of the updating is apparent from the fact that approximately half of the more than 7,000 references cited appeared since the last edition was published. Many new topics relevant to current assessment practices have been added to the 4th edition. The
Chapter on examination procedures, for example, now contains sections on cognitive functioning in pain and PTSD patients. The chapter on brain disorders includes new material on electrical/lightning injuries, migraine, Alzheimer's disease and other dementia disorders, and both medical and psychological treatments. The discussion of assessment procedures has been updated throughout to cover recently published test batteries used in general neuropsychological assessment (e.g., mental abilities, memory), newly developed batteries for specific issues (e.g., frontal lobe evaluation), and recent research on older neuropsychological assessment batteries. The fully revised chapter on assessing response bias describes and evaluates more than 60 tests, test combinations, and other measures for detecting questionable effort within the context of forensic neuropsychological assessment
Inhoudsopgave : Part I THEORY AND PRACTICE OF NEUROPSYCHOLOGICAL ASSESSMENT 1. The Practice of Neuropsychological Assessment
2. Basic Concepts 3. The Behavioral Geography of the Brain 4. The Rationale of Deficit Measurement 5. The Neuropsychological Examination: Procedures 6. The Neuropsychological Examination: Interpretation 7. Neuropathology for Neuropsychologists 8. Neurobehavioral Variables and Diagnostic Issues PART II A COMPENDIUM OF TESTS AND ASSESSMENT TECHNIQUES 9. Orientation and Attention 10. Perception 11. Memory I: Tests 12. Memory II: Batteries, Paired Memory Tests, and Questionnaires 13. Verbal Functions and Language Skills 14. Construction 15. Concept Formation and Reasoning 16. Executive Functions and Motor Performance 17. Batteries for Assessment of Brain Damage 18. Observational Methods, Rating Scales, and Inventories 19. Tests of Personal Adjustment 20. Testing for Functional Complaints Appendix References Test Index Subject Index
Keywords: Neuropsychological tests; Neuropsychologisch onderzoek; Psychologische tests